EFFECT OF STOCK MARKET DEVELOPMENT ON THE GROWTH OF CORPORATE BOND MARKET IN KENYA - Wanyama, Dr. David W. (International Journal of Finance, 2017)
Purpose: The purpose of this study was to analyze how stock market development influences the growth of corporate bond market in Kenya. Methodology: The study used descriptive and causal research designs. Secondary data was used. The sample of the study consisted of daily and monthly time series covering six years beginning January 2009 to December 2014. Unit root tests using Augmented Dickey-Fuller (ADF) and Phillips-Perron tests were done. The study used Eviews econometric software to facilitate empirical analysis of data. Results: Regression of coefficients results shows that Stock market size and corporate bonds are positively and significant related (r=0.029, p=0.002), stock market liquidity and corporate bonds are positively and significant related (r=8.291, p=0.0008), Stock Market Concentration and corporate bonds are positively and significant related (r=0.014, p=0.017). Regression of coefficients results shows that Stock Market Volatility and corporate bonds are positively and significant related (r=0.000023, p=0.0001). Unique Contribution to Theory, Practice and Policy: This study recommends study recommends for Policy makers to come up with measures to enhance the liquidity of the stock market which will in turn encourage investment in corporate bonds. The study recommends that concerted efforts should be made to improve market concentration in the corporate bonds market so that it can operate optimally. Policy makers should be aware of and monitor the level of stock market volatility that is appropriate for promoting the growth of the corporate bond markets and indeed other financial markets. Policy makers in Kenya should find ways and means of increasing the size of the stock market to reap the aforementioned benefits.